Multifunctional Visible‐Light Powered Micromotors Based on Semiconducting Sulfur‐ and Nitrogen‐Containing Donor–Acceptor Polymer. (23rd July 2020) - Kochergin, Yaroslav S.; Villa, Katherine; Novotný, Filip; Plutnar, Jan; Bojdys, Michael J.; Pumera, Martin
Abstract: Photosensitive micromotors that can be remotely controlled by visible light irradiation demonstrate great potential in biomedical and environmental applications. To date, a vast number of light‐driven micromotors are mainly composed from costly heavy and precious metal‐containing multicomponent systems, that limit the modularity of chemical and physical properties of these materials. Herein, a highly efficient photocatalytic micromotors based exclusively on a purely organic polymer framework—semiconducting sulfur‐ and nitrogen‐containing donor–acceptor polymer, is presented. Thanks to precisely tuned molecular architecture, this material has the ability to absorb visible light due to a conveniently situated energy gap. In addition, the donor‐acceptor dyads within the polymer backbone ensure efficient photoexcited charge separation. Hence, these polymer‐based micromotors can move in aqueous solutions under visible light illumination via a self‐diffusiophoresis mechanism. Moreover, these micromachines can degrade toxic organic pollutants and respond to an increase in acidity of aqueous environments by instantaneous colour change. The combination of autonomous motility and intrinsic fluorescence enables these organic micromotors to be used as colorimetric and optical sensors for monitoring of the environmental aqueous acidity. The current findings open new pathways toward the design of organic polymer‐based micromotors with tuneable band gap architecture for fabrication of self‐propelled microsensors for environmental control and remediation applications. Abstract : Herein, a fully organic polymer‐based micromotor is described. Due to the highly modular donor–acceptor molecular backbone, these microswimmers exhibit pronounced photocatalytic properties, and consequently, fuel‐free motion in pure water just under visible‐light illumination. Multiple functionalities, including photocatalytic degradation of organic pollutants and pH response enable new possibilities for fabrication of microscale devices for environmental monitoring and remediation applications.